"I cannot live without my [tablet]": Children's experiences of using tablet technology within the home. (May 2019) - Hadlington, Lee; White, Hannah; Curtis, Sarah
Abstract: The current study aimed to examine children's experiences of using tablet technology within the home. Eighteen children aged between eight and nine years old took part in four separate focus group discussions. Thematic analysis revealed three predominant themes: a battle of boundaries, a tool to escape the surrounding world, and an emerging dependency on tablet technology . The data implies that there is a growing dependency on tablet technology use among this age group. The current study also outlines that many children engage in a variety of techniques to circumvent parental limits on their tablet usage. However, other children discussed a lack of clear rules and restrictions for their use of tablet devices. The findings suggest that covert and unregulated use of tablet technology may have a detrimental impact upon children, particularly in relation to reduced social interaction, fatigue and increased family tensions due to excessive usage. Further research of child interactions with a wide variety of digital technology and media is warranted. Such exploration would further our understanding of the potential advantages and disadvantages for such technology use, as well as presenting a pathway to produce more effective guidance on home use. Highlights: Tensions exist between parents and children regarding domestic tablet device use. Varied and covert techniques were reported to evade any parental tablet limitations. Many children did not have clear boundaries for their home use of tablet technology. For some children tablet use may be problematic as symptoms of addiction were reported.